Literacy for sustainable development in the age of information - Rassool, Naz, 1949- (Language and education library, 1999)
"The book provides a critical overview of: the literacy debate in academic and general educational discourse, the role of functional literacy in societal development programmes during the past two decades, and a critical evaluation of the issues that surround literacy in an increasingly computer-dominated world." "The book's consideration of a reconceptualization of power within the information society, and its emphasis on 'communicative competence' in relation to democratic citizenship are unique. It makes an important contribution to the study of sociolinguistics, the sociology of technology, curriculum studies, the sociology of education and cultural studies. Its central focus on development in different societies will make it a useful text in Development Studies and Comparative Education."--Jacket